Diacoptic Method for Correction of Steady-State Conditions of Large Electrical Power System - K. V. Khachatryan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Diacoptic method for correction of complex EPS steady-state conditions is proposed in the paper. The paper considers the case when only excitation vector components or active and reactive power of load nodes are changed.